Prognosis after neoadjuvant chemoradiation or chemotherapy for locally advanced gastro-oesophageal junctional adenocarcinoma. Issue 11 (3rd September 2021) - Vos, E L; Carr, R A; Hsu, M; Nakauchi, M; Nobel, T; Russo, A; Barbetta, A; Tan, K S; Tang, L; Ilson, D; Ku, G Y; Wu, A J; et al.
Abstract: Background: Trials typically group cancers of the gastro-oesophageal junction (GOJ) with oesophageal or gastric cancer when studying neoadjuvant chemoradiation and perioperative chemotherapy, so the results may not be fully applicable to GOJ cancer. Because optimal neoadjuvant treatment for GOJ cancer remains controversial, outcomes with neoadjuvant chemoradiation versus chemotherapy for locally advanced GOJ adenocarcinoma were compared retrospectively. Methods: Data were collected from all patients who underwent neoadjuvant treatment followed by surgery for adenocarcinoma located at the GOJ at a single high-volume institution between 2002 and 2017. Postoperative major complications and mortality were compared between groups using Fisher's exact test. Overall survival (OS) and disease-free survival (DFS) were assessed by log rank test and multivariable Cox regression analyses. Cumulative incidence functions were used to estimate recurrence, and groups were compared using Gray's test. Results: Of 775 patients, 650 had neoadjuvant chemoradiation and 125 had chemotherapy. These groups were comparable in terms of clinical tumour and lymph node categories, although the chemoradiation group had greater proportions of white men, complete pathological response to chemotherapy, and smaller proportions of diffuse cancer, poor differentiation, and neurovascular invasion. Postoperative major complications (20.0 versus 17.6 per cent) and 30-day mortality (1.7 versus 1.6 per cent) were not significantly different between the chemoradiation and chemotherapy groups. After adjustment, type of therapy (chemoradiation versus chemotherapy) was not significantly associated with OS (hazard ratio (HR) 1.26, 95 per cent c.i. 0.96 to 1.67) or DFS (HR 1.27, 0.98 to 1.64). Type of recurrence (local, regional, or distant) did not differ after neoadjuvant chemoradiation versus chemotherapy. Conclusion: In patients undergoing surgical resection for locally advanced adenocarcinoma of the GOJ, OS and DFS did not differ significantly between patients who had neoadjuvant chemoradiation compared with chemotherapy. Lay Summary: Treating advanced cancer of the gastro-oesophageal junction (GOJ) poses a challenge given its location in the distal oesophagus and proximal stomach, and whether it should be treated as oesophageal or gastric cancer. Given the indistinct location, it is unclear whether GOJ cancer should be treated with neoadjuvant chemoradiation, which is the treatment of choice for advanced oesophageal cancers, or perioperative chemotherapy, which is the treatment of choice for advanced gastric cancers. Few studies have addressed treatment options specifically for GOJ cancers. This study investigated whether there was a difference in survival between patients with GOJ cancer who were treated with chemoradiation versus chemotherapy. Abstract : Cancer of the gastro-oesophageal junction (GOJ) is often grouped with either oesophageal or gastric cancer in trials, given its indistinct location in the distal oesophagus and proximal stomach. This retrospective study compared outcomes among 650 patients with adenocarcinoma of the GOJ treated with neoadjuvant chemoradiation and 125 who had neoadjuvant or perioperative chemotherapy. Neoadjuvant chemoradiation was not significantly associated with increased 30-day major complications or mortality, nor improved overall or disease-free survival, compared with perioperative chemotherapy.